Conjoined Twins in a Triplet Pregnancy: A Case Report. (6th September 2011) - Shepherd, Lynn J.; Smith, Graeme N.
Abstract : Background . Conjoined twins are a rare complication of monozygotic twinning and are associated with high perinatal mortality. Case . Here we present a case of conjoined twins in a triplet pregnancy diagnosed at 13 of weeks gestation. With the aid of 3D ultrasound and MRI images, the parents were counseled regarding the management options, including continuation of pregnancy, termination of pregnancy, or selective fetocide. They chose selective fetocide of the conjoined twins and went on to deliver the remaining triplet at term. Conclusion . This case represents to our knowledge the only MRI images of conjoined twins in a triplet pregnancy and demonstrates how 3D imaging can be used to better counsel patients about management options.